Real-time altitude control for a quadrotor helicopter using a super-twisting controller based on high-order sliding mode observer. (19th January 2017) - Gonzalez-Hernandez, Ivan; Palacios, Filiberto Munoz; Cruz, Sergio Salazar; Quesada, Eduardo Steed Espinoza; Leal, Rogelio Lozano
This article addresses the problem of altitude tracking for unmanned aircraft system when the altitude velocity is unknown, because in a practical implementation, the available sensors used to measure the vehicle's altitude (barometer, global positioning system, laser, etc.) do not provide the altitude velocity. We propose a control strategy based on both the super-twisting sliding mode controller as well as a high-order sliding mode observer to control and to estimate the altitude velocity, respectively. A comprehensive stability analysis for the combined controller–observer based on the Lyapunov stability theory is presented, ensuring the asymptotic convergence of the tracking error under external bounded disturbances. To demonstrate the performance and the effectiveness of the proposed solution, an extensive set of real-time experimental tests performed at outdoor environments is presented.